Determination of Aflatoxins in Feed by HPLC and PCR - Areej Zuhair Azeez; Mrwa Thamer Hindi; Maha Muhamed Khudiar; Adel Saadi AL Saadi; Noor Ibrahim Khadim (Journal of Food and Pharmaceutical Sciences, 2020)
The aim of this study is to identify aflatoxin secretion isolates in animal feeds by using HPLC and PCR  methods . In this study we collected fourty three samples of animal feed from different sites in Iraq (maize ,soybean ,sunflower grain ,barley grain, wheat). we isolated fungi  on potato dextrose agar, Aspergillus flavus  fungi was isolated from this samples  and identified the enzyme activities were tested for this isolate. The detection and determination for aflatoxin secretion of the isolates were done by using High Performance Liquid Chromatography (HPLC) technique. Twelve isolates shown Aflatoxin B1 secretion. Polymrease chain reaction ( PCR) technique is an alternative method to detect for Aspergillus spp. strains that secret aflatoxin by using specific primers( ITS1) endogenous gene for  Aspergillus flavus  and (ord , nor) genes  for aflatoxin B1 secreation, the PCR technique  considered to be an important role for safety and quality in industrial food and feed.